Reduction of Silent Information Regulator 1 Activates Interleukin-33/ST2 Signaling and Contributes to Neuropathic Pain Induced by Spared Nerve Injury in Rats - Zeng, Yanyan; Shi, Yu; Zhan, Hongrui; Liu, Wei; Cai, Guiyuan; Zhong, Haili; Wang, Yaping; Chen, Shangjie; Huang, Shimin; Wu, Wen (Frontiers in Molecular Neuroscience, 2020)
Emerging studies demonstrated that IL-33 and its receptor ST2 acted as a key factor in inflammatory disease. Besides, accumulating evidences evaluated that the cytokines TNF-α and IL-1β could trigger inflammatory cascade. Importantly, SIRT1 were validated to suppress the expression of inflammatory cytokines. However, whether the effects of SIRT1 on IL-33/ST2 signaling and IL-33 initiates the inflammatory cascade via modulating the TNF-α and IL-1β remain unclear. In the present study, we found that the DRG IL-33 and ST2 upregulated in SNI rats and intrathecal injection of either IL-33 antibody or ST2 antibody alleviated the mechanical allodynia and downregulated TNF-α and IL-1β induced by SNI. In addition, activation of SIRT1 decreased the enhanced DRG IL-33/ST2 signaling in SNI rats. Artificial inactivation of SIRT1 via intrathecal injection of SIRT1 antagonist could induce mechanical allodynia and upregulate of IL-33 and ST2. These results demonstrated that reduction of SIRT1 could induce upregulation of DRG IL-33 and ST2 and contribute to mechanical allodynia induced by SNI in rats.